Pola Hubungan Faktor Lingkungan Dengan Kejadian Chikungunya Di Wilayah Temanggung Jawa Tengah - Alwin; Este Latifahanun; Diena Nur Khayati; MB Ali Syaban (Pendidikan Geografi Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
In the world around 17% of human infectious diseases are caused by viruses transmitted anthropods such as chikungunya fever. Chikungunya fever is a disease caused by the Chikungunya virus (CHIKV), a type of ribonucleic acid virus (RNA) is transmitted through Aedes aegipty bites. Acute Chikungunya infection in humans can cause sudden fever, joint pain, rashes. Indonesian was reportedly 241 cases of Chikungunya cases in 2021, in the Temanggung Regency until 2022 there were no cases of Chikungunya. On July 26, 2022 there was a suspected Chikungunya in Temanggung I Village as many as 17 people Temanggung Health Center Work Area. The aims of study was to determine relationship between environmental factors and suspected chikungunya. Research used the quantitative with a case control design. The sampling technique uses a total sampling of 17 cases with a sample ratio of 1: 1 (17 cases and 17 controls), analyzed using the Chi-square test. The results showed that environmental factors variables presence of larvae (OR 5,958, p = 0.016), presence water reservoirs (or 4,643, p = 0.037), presence of waste (OR 4,400, p = 0.039), and occupancy density (OR 5,760, p = 0.016) has a significant pattern of relationship with the suspected Chikungunya.